Kinerja Organisasi Publik dalam Mendukung Penyelenggaraan Pelayanan di Kantor Kecamatan Johan Pahlawan - Agatha Debby Reiza Macella (Universitas Teuku Umar, 2020)
The focus of this research is the organizational performance of Johan Pahlawan District in supporting the delivery of public services. The purpose of this study is to find out how the organization's performance and the factors that influence the performance of Johan Pahlawan sub-district in supporting public services there. The research method used in the writing of this paper is descriptive qualitative with documentation study data collection techniques. The performance of employees in the Johan Pahlawan District Office organization is seen from 5 indicators namely productivity, service quality, responsiveness, responsibility and accountability. Every employee, both superiors and subordinates, is always based on the SOP that has been applied in the Johan Pahlawan sub-district office. The limited facilities and infrastructure as well as the limited ability of the apparatus to be less than the maximum implementation of public services in the district office. Accountability of Johan Pahlawan sub-district is done internally and not yet published online because it does not yet have its own website. Factors affecting the performance of Johan Pahlawan Sub District include equipment and technology used, internal conditions of employees, and inadequate facilities and infrastructure.